Relation between Plasminogen Activator Inhibitor-1 and Hepatic Enzyme Concentrations in Hyperlipidemic Patients - Bruckert, E; Ankri, A; Glral, P; Turpin, G (Thrombosis and Haemostasis, 1994)
Plasminogen activator inhibitor type-1 (PAI-1) is a key determinant of the fibrinolytic capacity. Its activity correlates with most of the characteristic features of insulin resistance syndrome, i. e. obesity, high blood pressure and hyperlipidemia.We measured plasma PAI-1 antigen levels in 131 asymptomatic men (aged 44.2 ± 11 years) who had been referred for hyperlipidemia. Those taking medication and those with a secondary hyperlipidemia were excluded.We confirmed the correlation between PAI-1 levels and the following variables: body mass index, blood pressure, triglyceride concentration, and blood glucose and insulin levels before and after an oral glucose tolerance test. We also found a significant and independent correlation between PAI-1 and the concentration of the hepatic enzymes glutamyl transferase, alanine aminotransferase and aspartate aminotransferase.Mild liver abnormalities (presumably steatosis) may thus be one of the factors accounting for high plasma PAI-1 levels in hyperlipidemic patients.